2018
DOI: 10.4236/jss.2018.66001
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Fatigue on Work-Life Balance and Positive Well-Being in Railway Staff

Abstract: Both fatigue and negative work-life balance can be influenced by job characteristics and individual differences, while fatigue is associated with reduced positive well-being. This paper reports a study that investigated the mediation effect of fatigue between those stressors and well-being outcomes among UK railway staff. A large number of significant mediation effects of fatigue were found in this study, and as a result, the process by which job demands, job support and control influence major positive well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Overall, this pattern of the results confirms the utility of the Student WPQ and suggests that it can be used in either its full or short form. Similar results have been obtained with other measures of wellbeing based on the wellbeing process model [12][13][14][15][16][17][18][19].…”
Section: Resultssupporting
confidence: 85%
“…Overall, this pattern of the results confirms the utility of the Student WPQ and suggests that it can be used in either its full or short form. Similar results have been obtained with other measures of wellbeing based on the wellbeing process model [12][13][14][15][16][17][18][19].…”
Section: Resultssupporting
confidence: 85%
“…It proposed that the subjective appraisal of fatigue could mediate the relationship between the environment and the outcomes. A recent study (Fan and Smith, in press ) has found such a mediating effect of fatigue. Although this model also suggested that individual differences may moderate the relationships between environment, fatigue and outcomes, this a moderating effect was not found in subsequent studies (e.g., Capasso et al, 2016 ).…”
Section: Introductionmentioning
confidence: 87%
“…The data were transferred to the IBM SPSS version 27 statistical package for analysis. The survey included questions about working away strategies, quality of working life, and the Smith Well-being Questionnaire [SWELL, [20][21][22]. Initial analyses examined the factor structure of working away strategies, quality of working life, and the well-being outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Negative factors such as job demands and negative coping strongly predict stress, anxiety and depression, whereas the absence of positive factors may have a smaller association with these negative outcomes. Health and safety outcomes (e.g., work efficiency; absenteeism, presenteeism and accidents) were also added, as were questions about a healthy lifestyle (the Smith Well-being Questionnaire, SWELL, [19][20][21].…”
Section: The Well-being Process Modelsmentioning
confidence: 99%